The effects of Tualang honey on sperm profile In mixed cholesterol diet administered rats - Hasan, Sakiinah; Abdul Rahim, Roslina; Alias, Mohd Afzal; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Abdul Razak, Redzuan Nul Hakim (2021)
Introduction: Hypercholesterolaemia is a recognised factor associated with male infertility. They have been shown to reduce the semen quality. The main recommendation for treatment is diet modifications. Tualang honey (TH) has proven to exert anti-inflammatory and anti-oxidative effects which may help to improve sperm parameters. Methods: Thirty male Sprague Dawley rats were divided into two groups, mixed cholesterol diet (12%CD;n=24) and standard diet (SD;n=6) and were fed for 16 weeks. Then, the rats in the 12%CD group were divided into four groups and continued with SD. Group A was untreated while group B, C and D were given TH at different doses (1.2, 2.4, and 3.0g/kg/day) for 4 weeks. Then, sperm profile analysis from the caudal epididymis was performed. Results: Group A showed significant decrease in sperm concentration, the percentage of total sperm motility, progressive motility, and viability compared to SD group (p<0.001). In contrast, all TH supplemented groups demonstrated significant improvement in the sperm parameters (p<0.001). The higher the dosage of TH given, the higher the improvements in sperm parameters (p<0.001). Conclusion: TH supplementation with diet modifications improved sperm profile parameters. From our findings, there is a need to further explore TH in improving male infertility associated with hypercholesterolaemia.